Study of thresholds to burning in surface grinding process - De Aguiar, P. R. [UNESP]; Dotto, F. R L [UNESP]; Bianchi, E. C. [UNESP] (Springer Nature, 2005)
This work aims at finding out the threshold to burning in surface grinding process. Acoustic emission and electric power signals are acquired from an analog-digital converter and processed through algorithms in order to generate a control signal to inform the operator or interrupt the process in the case of burning occurrence. The thresholds that dictate the situation of burn and non-burn were studied as well as a comparison between the two parameters was carried out. In the experimental work one type of steel (ABNT-1045 annealed) and one type of grinding wheel referred to as TARGA model 3TG80.3-NV were employed. Copyright © 2005 by ABCM.
Keywords: Acoustic emission; Burning; Electric power; Grinding; Monitoring; Acoustic wave propagation; Algorithms; Analog to digital conversion; Control systems; Crack initiation; Electricity; Grinding (machining); Statistical methods; Steel; Surface treatment; Control signals; Combustion